Study on the Optimal Factors for Briquetting Charcoal from Coconut Shells Using a Full Factorial Experimental Design - Cheewaworanontree, Yossawat; Thongsin, Kridtharit; Rontlaong, Piya (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2026)
This research aimed to investigate the optimal factors for compressing coconut shell charcoal briquettes using a full factorial design (2k full factorial design). A coconut shell charcoal briquette compressing machine was developed with a width of 60 cm, a length of 66 cm, and a height of 149 cm. The machine employed a semi-automatic power transmission system driven by a 7.5-horsepower electric motor (380 V), equipped with a 3.5-inch drive pulley and a 21-inch driven pulley. The experimental design consisted of three factors: screw length (30-32 cm), compression cylinder size (45-47 mm), and motor speed (254-267 rpm). The experiment was repeated three times with 30 samples per trial, resulting in a total of 24 experimental runs. The results indicated that the optimal conditions for briquette compression were a screw length of 30 cm, a compression cylinder size of 45 mm, and a motor speed of 254 rpm. These optimal factors were subsequently applied in an additional experiment to collect comparative data. The results showed that, prior to optimization, 19 briquettes (21.10%) were broken or insufficiently compacted, whereas after optimization the number decreased to 8 briquettes (8.90%), representing a reduction of 11 briquettes (57.89%).